Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2006
DOI: 10.1145/1124772.1124830
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a fisheye view of source code

Abstract: Navigating and understanding the source code of a program are highly challenging activities. This paper introduces a fisheye view of source code to a Java programming environment. The fisheye view aims to support a programmer's navigation and understanding by displaying those parts of the source code that have the highest degree of interest given the current focus. An experiment was conducted which compared the usability of the fisheye view with a common, linear presentation of source code. Sixteen participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 20 publications
4
44
0
Order By: Relevance
“…We suggest making the context region of the interfaces more informative by including more readable or otherwise useful information. Our multifocus menu is one example, while the interface presented by Jakobsen and Hornbaek [2006] is another.…”
Section: General Implications For Fisheye Interfacesmentioning
confidence: 99%
“…We suggest making the context region of the interfaces more informative by including more readable or otherwise useful information. Our multifocus menu is one example, while the interface presented by Jakobsen and Hornbaek [2006] is another.…”
Section: General Implications For Fisheye Interfacesmentioning
confidence: 99%
“…A number of approaches have been suggested for wholeprogram visualization and navigation [4,7,12,18,40]. Some approaches have made efforts to restrict the information presented so as not to overwhelm the developer by adding zooming or fisheye viewing capabilities [7,18,40] or aggregating dependencies to a higher level [4].…”
Section: Program Structure Visualizationmentioning
confidence: 99%
“…However, only five of the 19 studies reported usage patterns, constructed either based on non-intrusively collected interactivity recordings such as eye-tracking records [21,16] or navigation action logs [13,15,17].…”
Section: Capture Usage Patternsmentioning
confidence: 99%